Pulsed laser deposition of ZnSe:N epilayers - "Boo, Bong Hyun"; "Lee, Jae Kwang [Chungnam National University, Taejon (Korea, Republic of)]" (KAERI, Taejon (Korea, Republic of), 1999)
We have grown epitaxial of nitrogen doped ZnSe films on GaAs(100) substrates by pulsed laser deposition (PLAD) assisted by an nitrogen beam produced by a supersonic nozzle beam source. Atomic force microscopy (AFM) shows that the surface of an ZnSe epilayer grown on Ga As(100) at 10{sup -3} torr is flat and dense and its roughness is about 1.6 nm, less than that of some good quality MOVPE-grown samples. X-ray diffraction (XRD) results show that this ZnSe epilayer is of a fine characteristics of single crystallinity. X-ray photoelectron spectroscopy (XPS) indicates that the epilayer are composed of 84 percent Zn and Se, 10 percent N, and 6 percent O, and other kinds of impurities are scarcely in existence. XPS spectra involving Zn(2p{sub 3/2}) and N(1s) core level indicate that doped nitrogen atoms with an estimated concentration of over 10{sup 21} cmsup 3 exist in the as-grown epilayer. (author)
Keywords: "75 CONDENSED MATTER PHYSICS, SUPERCONDUCTIVITY AND SUPERFLUIDITY"; "DOPED MATERIALS"; "ENERGY BEAM DEPOSITION"; "LASER BEAM MACHINING"; "X-RAY DIFFRACTION"; "X-RAY SPECTROSCOPY"; "ZINC SELENIDES"